Climate change impacts on electricity demand: The case of a Southern European country. (December 2020) - Silva, Susana; Soares, Isabel; Pinho, Carlos
Abstract: We study the relationship between average temperatures and electricity consumption in Portugal. Control variables include electricity prices and the economic activity. Our results indicate that there is U-shaped relationship between temperature and electricity consumption. While changes in average temperature do not affect electricity consumption by a large extent, extreme temperatures have stronger impacts. Given the mild weather in Portugal, electricity demand has not changed significantly over the last decades. Larger impacts can only be expected if extreme weather events become more frequent. Our results show the importance of considering country specificities in the analysis and of comparing several model specifications. Highlights: Climate change may affect electricity demand through heating and cooling needs. We relate temperatures and electricity consumption in Portugal. Results show a U-shaped relation between temperature and electricity consumption. Extreme temperatures have stronger effects than changes in moderate ones. It is key to consider country specificities.